2020
DOI: 10.1111/pbi.13448
|View full text |Cite
|
Sign up to set email alerts
|

R2R3 MYB‐dependent auxin signalling regulates trichome formation, and increased trichome density confers spider mite tolerance on tomato

Abstract: Unicellular and multicellular tomato trichomes function as mechanical and chemical barriers against herbivores. Auxin treatment increased the formation of II, V and VI type trichomes in tomato leaves. The auxin response factor gene SlARF4, which was highly expressed in II, V and VI type trichomes, positively regulated the auxin-induced formation of II, V and VI type trichomes in the tomato leaves. SlARF4 overexpression plants with high densities of these trichomes exhibited tolerance to spider mites. Two R2R3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 51 publications
(73 reference statements)
4
29
0
Order By: Relevance
“…Hase et al [17,63] showed that the frequency of DNA mutations, including single-substitutions, small InDels, and DNA structural variation, increased when irradiation was applied at higher doses. Trichomes are specialized cells that undergo differentiation from the epidermis of plants and play an essential role in conferring protection to plants against various biotic and abiotic stresses [64][65][66]. We detected a decrease in the density of type VI trichomes on leaves when gamma rays were used for chronic irradiation at a dose of 100-200 Gy for 4 weeks.…”
Section: Discussionmentioning
confidence: 84%
“…Hase et al [17,63] showed that the frequency of DNA mutations, including single-substitutions, small InDels, and DNA structural variation, increased when irradiation was applied at higher doses. Trichomes are specialized cells that undergo differentiation from the epidermis of plants and play an essential role in conferring protection to plants against various biotic and abiotic stresses [64][65][66]. We detected a decrease in the density of type VI trichomes on leaves when gamma rays were used for chronic irradiation at a dose of 100-200 Gy for 4 weeks.…”
Section: Discussionmentioning
confidence: 84%
“…The GLABRA 1 (GL1)-GLABRA 3 (GL3)/ENHANCER OF GLABRA 3 (EGL3)-TRANSPARENT TESTA GLABRA 1 (TTG1) trichome development complex has been well studied ( Zhao et al, 2008 ); however, knowledge of the interaction between this complex and phytohormones is limited. Sweet wormwood ( Artemisia annua ), tomato ( Solanum lycopersicum ), and cucumber ( Cucumis sativus ) are the main plant species used as models for studying glandular trichome development ( Lv et al, 2017 ; Du et al, 2020 ; Xiong et al, 2020 ), and many studies have indicated that trichome development involves phytohormones ( Yan et al, 2017 ; Chen et al, 2020 ; Yuan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In tomato, THM1, a R2R3 MYB transcription factor, acts as a negative regulator of long trichomes [ 74 ]. To explore the relationship between THM1 and H/HL, we examined the transcriptional level of THM1 in mutants of h , hl , and h / hl h .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, JAZ2 can block the activity of H and HL in the repression of THM1 expression. THM1 has been shown by previous studies to regulate auxin-induced trichome formation [ 74 ]. In the Y2H assay, H/HL could interact with multiple JAZ proteins ( Fig.…”
Section: Discussionmentioning
confidence: 99%